Genetic variation among Stevia rebaudiana bertoni genotypes under light treatment on morpho-agronomic traits and issr molecular markers - Abdulameer, Dhulfiqar Aamer (2018)
Stevia rebaudiana Bertoni is a perennial herb with natural sweetening compounds that are 230 times sweeter than sucrose with no calorific value. It belongs to the family Asteraceae (Compositae) and is native to Paraguay. It is a good source of carbohydrates, protein, crude fibers and minerals. Stevioside and rebaudioside A are the two major sweetening compounds. Stevia is a short day plant which form flowers when day length is less than 12 hours and it is resulting in low biomass production. In this study, a set of stevia genotypes collected from different sources were evaluated for yield components and flowering characteristics both under short day length (12 hours) and long day length (14 hours) environments. Genetic variation among those genotypes was also investigated using ISSR molecular markers. A total of twenty-six stevia genotypes including two hybrids were collected. The propagation of all collected stevia genotypes was achieved through stem microcutting within six months. Eight genotypes namely, CHV1, Morita2, MS012, MS012 (4x), SA18, TPU, and hybrids IIUM-F1 and UiTM-F1 which had shown good propagation ability under mist-chamber propagation boxes and were evaluated for the agronomic performance under short day length (12 hours) and long day length (14 hours) environments using a split plot design. In general, all the agronomic characteristics of pooled genotypes were increased significantly under the extended light (14 hours). Stevia plants under sunlight (12 hours) started to flowering after 52 days after transplanted. On the other hand stevia plants under extended light were not flowered up to 134 days at harvesting stage. Combined biomass fresh weight mean of the eight genotypes was increased 728% under extended light compared to genotypes kept under sunlight. The biomass fresh weight mean and plant height of genotype SA18 was the highest in both extended and sunlight conditions (35.82 g and 3.96 g; 92.47 cm and 24.92 cm respectively). The Pearson correlation coefficient showed that biomass fresh weight had strongly positively correlated with all the characters except number of branches. Genetic variation and cluster analysis based on ISSR markers showed that genotypes CHV1 and H2 were the most closely related genotypes with the highest similarity index (54%). On the other hand, genotypes MS012 and TPU were the distantly related genotypes with the lowest similarity index (24%). In conclusion, stevia plants kept under extended light showed better performance than under sunlight. Three genotypes, SA18, TPU and CHV1 were shown better performance than other genotypes, and are recommended for further utilization in future stevia breeding programs.